FROM SCROLLING TO STRUCTURING: THE ROLE OF MOBILE AI TOOLS IN IDEA GENERATION FOR ESL WRITING AMONG GENERATION Z LEARNERS - Muratova Khurshida Ne’matullo qizi (TADQIQOTLAR, 2025)
Abstract The  shift  to  mobile-assisted  learning  has  dramatically  influenced  writing instruction  in  English  as  a  Second  Language  (ESL)  classrooms,  especially  among Generation Z learners. This paper explores how mobile-based AI tools, specifically ChatGPT, serve as catalysts for idea generation in ESL writing instruction. Grounded in digital learning theories and constructivist pedagogy, the study examines practical classroom  applications  of  ChatGPT  on  mobile  devices  and  surveys  learners' perceptions. The findings suggest that mobile AI tools help ESL students overcome idea-generation  blocks,  promote  learner  autonomy,  and  enhance  cognitive engagement. Pedagogical implications and ethical considerations are discussed.